Investigating the feasibility of a locally developed carbon-offsetting scheme : the case of the Drifters Desert Nature Reserve - Gibson, Sean (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.